2003
DOI: 10.1081/pln-120017144
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Cadmium Uptake and Phytotoxic Levels of Zinc in Hard Red Spring Wheat

Abstract: Wheat grown on cadmium (Cd)-uncontaminated soils can still potentially translocate unacceptable levels of Cd to grain. The effect of zinc (Zn) and Cd levels on Cd uptake and translocation in ''Grandin'' hard red spring wheat (HRS-wheat) (Triticum aestivum L.) was investigated using a double chelator-buffered nutrient solution [EGTA used to buffer Cd, Zn, copper (Cu), manganese (Mn), and nickel (Ni); and Ferrozine (FZ) used to buffer Fe 2þ ]. In the Zn level series of treatments, Cd 2þ activity was held constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Zinc could be added to soil contaminated with Cd to help reduce Cd in food crops. In fact, Green et al (2003) did an experiment which indicated that it might be possible to reduce Cd in wheat by adding Zn. They studied the effect of Cd and Zn levels on Cd uptake and translocation of wheat (Triticum aestivum).…”
Section: Zincmentioning
confidence: 96%
See 1 more Smart Citation
“…Zinc could be added to soil contaminated with Cd to help reduce Cd in food crops. In fact, Green et al (2003) did an experiment which indicated that it might be possible to reduce Cd in wheat by adding Zn. They studied the effect of Cd and Zn levels on Cd uptake and translocation of wheat (Triticum aestivum).…”
Section: Zincmentioning
confidence: 96%
“…They studied the effect of Cd and Zn levels on Cd uptake and translocation of wheat (Triticum aestivum). Genotypes of wheat can tranloscate high enough levels of Cd from uncontaminated soils to exceed the regulatory limits, which the Food and Agricultural Organization of the United Nations (FAO) suggests ought to be 0.1 mg Cd kg − 1 for cereal grains (Green et al, 2003). They found that the level of Cd did not affect the uptake and translocation of Zn in the roots and shoots.…”
Section: Zincmentioning
confidence: 97%
“…Similar results were reported by Castaldi et al (2009) who found that translocation for wheat and pea followed the order Cd > Pb. High Cd translocation was found in plants because of its similar properties to Zn (Liphadzi and Krikham 2006), and Cd translocation in wheat (Triticum aestivum L.) was regulated by Zn (Green et al 2003). Low translocation of Pb was found in plants because Pb was sequestered in the vacuole or cell walls in the root (Castaldi et al 2009), which was related to stability property of Pb in soil-plant system.…”
Section: Translocation Factor and Bioconcentration Factormentioning
confidence: 99%
“…Yang et al (2011) reported that application of foliar Zn or seed-soaking Zn fertilizers decreased Cd concentrations in cucumbers by 12-36%. Similarly, Zn fertilizers could decrease Cd concentrations in the shoots of bread and durum wheat (Green et al 2003;Koleli et al 2004). Therefore, the addition of amendments or extra fertilizers is a promising and sustainable strategy for remediation of heavy metalcontaminated soils, which can not only effectively immobilize Cd and Pb in soils but also improve soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…was resistant to lead despite using a transporter protein and phosphates [15]. Soil microorganisms interact with plants in many different ways to reduce metal ion toxicity and enhance metal ion absorption by plants [16]. Likewise, Kumar et al [17] studied the ability of four acclimated microorganisms to accumulate heavy metals and concluded that Pseudomonas sp.…”
Section: Identification Of Rhizobacteriamentioning
confidence: 99%